Pengaruh Penambahan Enkapsulasi Ekstrak Daun Afrika (Vernonia Amygdalina) dalam Air Minum terhadap Performa Broiler: Effect of Adding Encapsulation of African Leaf Extract (Vernonia amygdalina) In DrinkingWater on broiler chicken Performance - Siagian, Abel; Nelzi, Nelzi; Arisya, Wahyu (BPFP Universitas Bengkulu, 2025)
The purpose of this study was to determine how broiler performance with the addition of African leaf extract (Vernonia amygdalina) encapsulation in drinking water affects broiler performance, including feed consumption, body weight gain, ration conversion, and drinking water consumption. This study used a Completely Randomized Design (CRD) method with five treatments (A = control, B = EEDA 0.5%, C = EEDA 1%, D = EEDA 1.5%, and E = EEDA 2%) and four replications, each consisting of five chickens. Encapsulation was carried out using the foam mat drying method with Tween 80 and maltodextrin coating materials. The results showed that the addition of African leaf extract encapsulation contributed significantly (P <0.05) to increasing feed conversion efficiency and body weight gain, as well as to decreasing feed and drinking water consumption. The addition of EEDA in drinking water affected body weight gain, feed consumption, feed conversion, and drinking water consumption. The addition of 0.5% EEDA in drinking water is the best dose that can increase body weight, ration consumption, and improve ration efficiency.